JOB SATISFACTION AMONG EMPLOYEES WITH CHRONIC ILLNESS AND RESULTANT WORK DISABILITY: EFFECT OF EMPLOYER RELATED VARIABLES (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
The study has attempted to explore the  relationship between disability and job  satisfaction among employees with chronic  illnesses and disability in the Indian  organizations (Delhi NCR, India). The  direct correlation statistic for disability and  job satisfaction was weak and negative. To  explore the relationship further, the role  of industry wise differences and size of the  organizations (based on number of employees)  in the relationship of the disability and job  satisfaction among this group was examined  using hierarchical regression analysis. The  results suggest strong moderation effect of  industry sector of the organization in the  relationship between disability and job  satisfaction of employees with chronic illness  and disability.
Keywords: Chronic Illness,; disability; job satisfaction; distinct diversity group; industry wise differences; employer-related variables.